Oxygen-dependent subcellular redistribution of PHD3 links the hypoxic microenvironment to mitochondrial metabolic reprogramming in ccRCC - Jaelim Sim; Soyeon Lim; Changjun Lee; Hani Jieun Kim; Wonseok Lee; Hyeonki Kim; Hojun Lee; Kimyeong Kim; Mahesh Kumar Teli; Kyeong Beom Jo; Jacob Wright; Jee Soo Park; et al. (Experimental & Molecular Medicine, 2026)
Abstract Clear cell renal cell carcinoma (ccRCC) is characterized by profound metabolic dysregulation, with both prolyl hydroxylase domain protein 3 (PHD3) and pyruvate carboxylase (PC) independently implicated in disease progression. Although each influences patient outcomes, a direct mechanistic interplay between these two regulators has remained elusive. Here, we uncover a novel regulatory axis involving PHD3 and PC by identifying an unexpected subcellular behavior of PHD3, namely, its dual localization to the cytosol and the mitochondrial matrix. We show that mitochondrial import of PHD3 is associated with its intracellular clustering, a process modulated by PHD3 hydroxylase activity and oxygen levels. Once in the matrix, PHD3 directly hydroxylates PC, suppressing its enzymatic activity. In ccRCC with elevated PHD3 expression, this modification restricts anaplerotic flux into the tricarboxylic acid cycle, leading to impaired proliferation, reduced metastasis, and enhanced apoptosis. Together, our findings provide a new framework for targeting cancer metabolism by establishing a previously unrecognized mechanistic link between PHD3-mediated oxygen sensing within the tumor microenvironment and the regulation of ccRCC mitochondrial metabolism through the subcellular re-localization of PHD3.